Equity in sustainable development: Community responses to environmental gentrification. (27th May 2020) - Krings, Amy; Schusler, Tania M.
Abstract : Sustainable development aims to address economic, social, and environmental imperatives; yet, in practice, it often embodies a neoliberal market logic that reinforces inequalities. Thus, as the social work profession grapples with its role in advancing environmental sustainability, practice models must explicitly attend to social and economic justice. For example, environmental gentrification refers to situations in which the cleanup of contaminated land or the installation of environmental amenities intentionally or unintentionally catalyzes increased housing costs, thereby contributing to the displacement of vulnerable residents. With the goal of contributing to practice knowledge, we conducted a systematic review of peer‐reviewed articles (1997−2017) to learn how community groups have responded to the threat of environmental gentrification. We found that community organizations employ a range of strategies, including blocking development, negotiating for protections, planning alternatives, and allying with gentrifiers. We conclude by exploring ethical implications and practice principles to help social workers engage in truly sustainable development. Key Practitioner Message: The term environmental gentrification describes situations where improvements to environmental quality increase real estate prices, contributing to the displacement of vulnerable residents ; An environmental justice framework attending to procedural, distributional, and recognition-based claims provides a model for social work practice; Opportunities exist for social workers to take an intersectional rather than siloed approach to integrate economic, social, and environmental concerns.